The retrospective experiences of persons with substance use disorders and the members of an interdisciplinary team regarding the provision of treatment services during a biological disaster in the Gauteng Province, South Africa - Geyer, Stephan (University of Pretoria, 2025)
Thesis (PhD)--University of Pretoria 2025.